Hypogravity modeling of upper extremities: an investigation of manual handling in the workplace - Maillard, Tatiana (Frontiers in Physiology, 2023)
Experiments on the lower limbs are the only ones being used to study how hypogravity (0 < g < 1, e.g., Moon: 1/6 g, Mars: 3/8 g) affects human movement. The goal of this study was to expand this field experimentally by investigating the effect of hypogravity on the upper extremities during onehand manual handling tasks in a sitting posture: static weight holding with an outstretched arm and slow repetitive weight lifting and lowering motions. The hypothesis was that while completing static and dynamic tasks with elements of repetition in hypogravity, the upper body's tilt (angle regarding the vertical) would change differently from Earth's gravity. Specifically, upper arm and spine angles, joint torques, and forces were investigated. Twenty-four healthy participants aged 33.6±8.2 years were involved in the trial. Joint angles were examined using vision-based 3D motion analysis. According to this investigation, there is a correlation between a body tilting backward and a gravity level reduction (p<0.01). Thus, hypogravity causes postural deviation, and this shows that workplace design must be adapted according to the level of gravity to promote comfortable and balanced body alignment, minimizing stress on muscles and joints. To lower the risk of musculoskeletal disorders, enhance overall performance, and increase job satisfaction, proper support systems and restrictions for sitting positions should be taken into consideration concerning different levels of gravity.